T106. Warming nerves for excitability-testing - Kovalchuk, Maria O.; Scheijmans, Féline E.; van Schelven, Leonard J.; Franssen, Hessel; Sleutjes, Boudewijn T. (Clinical neurophysiology, 2018)
Temperature affects excitability-variables measured from peripheral nerve. Excitability studies provide valuable insights into disease mechanisms in motor neuron disease and various neuropathies. Warming the nerve prior to the investigation helps to compensate for temperature variability, facilitates reproducibility, and improves the certainty of ascribing changes to pathophysiological mechanisms. For clinical purposes, therefore, it is important to determine how long a nerve has to be warmed for an excitability-variable to reach a stable value. We investigated which method of warming the nerve was quickest in reaching stable excitability variables. In five healthy subjects, we compared three methods of warming the median nerve to 37 °C: (i) infrared lamp, (ii) water blanket, and (iii) water bath. Prior to warming the nerve, an excitability test was performed in all three methods to assess baseline values for distal motor latency (DML) and multiple excitability variables (strength duration time constant, rheobase, minimal and resting I/V slope, relative refractory period and super-excitability). During a one-hour warming period, the excitability-tests were repeated every 10 min from which the values for DML and excitability variables were determined. To asses which were affected by temperature in our subjects, we first investigated the temperature relation for all recorded variables. Temperature dependent variables were fitted by an exponential function from which the time-constant and asymptotic end-value were determined. A variable was considered to be stable when it had reached 95% of the asymptotic end-value. Temperature-dependency was found for DML, refractory period and super-excitability. Of the three warming methods, the water bath was the quickest in reaching stable values for DML (29 min, IQR 22–30), refractory period (25 min, IQR 23–33), and super-excitability (43 min, IQR 43–49). For the infrared lamp, DML reached stable values at 36 min (IQR 30–42), refractory period at 28 min, IQR 27–32), and super-excitability at 45 min, IQR 36–51). For the water blanket stable values were reached for DML at 36 min (IQR 23 – 52), for refractory period at 34 min (IQR 29–35), and for super-excitability at 45 min (IQR 25–71). Warming the median nerve in a water bath is the most efficient way to warm the nerve for excitability-testing.